Dinâmica de uso do solo na Reserva Extrativista Ipaú-Anilzinho e entorno, Pará, 1993-2019 - Moraes, Lucélia Gonçalves (2021)
This research focused on the Ipaú-Anilzinho Extractive Reserve, near the town of Baião, Pará, in the Brazilian Amazon. It is a federal conservation unit that does not yet have an official management plan. Complex land conflicts occur in its territory and surroundings, and thus need for adequate management strategies. Our aim was to analyze the dynamics of land use and cover in the Reserve territory, and in its immediate surroundings (10 km buffer), between 1993 and 2019. Landsat satellite images were used for supervised classification with the MaxVer algorithm. By means of geoprocessing techniques, digital thematic maps were prepared for land use and land cover in the years 1993, 1999, 2005, 2010, 2015 and 2019. The results obtained were compared with the data available on the MapBiomas platform, in order to validate the generated information. The accuracy of the classification was defined by the Kappa index, with a global value of 0.87, indicating excellent agreement of the analyzed results. Over 26 years, there was a reduction in native vegetation cover of 5.89% inside the Extractive Reserve, and 7.12% in the surrounding area. The results suggest a greater environmental impact in the southern portion of the Reserve, and show pastures as the main land use, in expansion. The information generated in this work can subsidize the management of the territory, in the preparation of the official Management Plan, as well as be used as a basis for proposing agreements with resident communities, and for the elaboration of public policies or practical solutions to contain deforestation caused by agricultural and cattle raising expansion that has been taking place at the site.